Spatio-temporal delivery of both intra- and extracellular toll-like receptor agonists for enhancing antigen-specific immune responses - Nannan Wang; Yueyue Zuo; Shengjie Wu; Chenlu Huang; Linhua Zhang; Dunwan Zhu (Elsevier, 2022)
For cancer immunotherapy, triggering toll-like receptors (TLRs) in dendritic cells (DCs) can potentiate antigen-based immune responses. Nevertheless, to generate robust and long-lived immune responses, a well-designed nanovaccine should consider different locations of TLRs on DCs and co-deliver both antigens and TLR agonist combinations to synergistically induce optimal antitumor immunity. Herein, we fabricated lipid-polymer hybrid nanoparticles (LPNPs) to spatio-temporally deliver model antigen ovalbumin (OVA) on the surface of the lipid layer, TLR4 agonist monophosphoryl lipid A (MPLA) within the lipid layer, and TLR7 agonist imiquimod (IMQ) in the polymer core to synergistically activate DCs by both extra- and intra-cellular TLRs for enhancing adaptive immune responses. LPNPs-based nanovaccines exhibited a narrow size distribution at the mean diameter of 133.23 nm and zeta potential of −2.36 mV, showed a high OVA loading (around 70.83 μg/mg) and IMQ encapsulation efficiency (88.04%). Our data revealed that LPNPs-based nanovaccines showed great biocompatibility to immune cells and an excellent ability to enhance antigen internalization, thereby promoting DCs maturation and cytokines production. Compared to Free OVA, OVA-LPNPs promoted antigen uptake, lysosome escape, depot effect and migration to secondary lymphatic organs. In vivo immunization showed that IMQ-MPLA-OVA-LPNPs with dual agonists induced more powerful cellular and humoral immune responses. Moreover, prophylactic vaccination by IMQ-MPLA-OVA-LPNPs effectively suppressed tumor growth and increased survival efficacy. Hence, the nanovaccines we fabricated can effectively co-deliver antigens and different TLR agonists and realize coordinated stimulation of DCs in a spatio-temporal manner for enhanced immune responses, which provides a promising strategy for cancer immunotherapy.